Eating disorders and their impact during the gestational period - Silva, Fernanda B.; Pietro, Luciana (Brazilian Journal of Health and Biomedical Sciences, 2022)
Introduction: Eating disorders can cause numerous problems for the physiology of the female body and consequences, such as infertility and difficulties during pregnancy and childbirth, can occur if they are present during a woman’s reproductive age. Objective: The objective of this research was to analyze the impacts for mother and child that may be somehow related to the nutritional deficiency, whether active or not, of these women. Methodology: The methodology used was a bibliographic survey in the platforms PubMed, BIREME, SCIELO, using combinations of the following keywords in English: Eating Disorder AND Pregnancy, Anorexia, Bulimia. Result: According to the studies analyzed, the existence of some type of eating disorder, whether active or not, had a negative impact on the pregnancies of these women. Miscarriages, stillborn babies, premature birth, premature placental displacement, small newborn gestational age, umbilical cord knots and even neurological deficits could occur. Discussion: Low body mass index (BMI) was one of the main subjects of discussion in the studies, since it can increase the risk of pregnancy because the mother’s nutrients are crucial for a healthy gestation. Thus, it was concluded that medical, nutritional and psychological follow-up are essential for women with eating disorders, regardless of type, to be able to have a safe pregnancy for themselves and their babies. Keywords: Eating disorders; Mother-child impacts; Nervous bulimia; Anorexia nervosa; Gestational complications.